HUBUNGAN TINGKAT STRESS DENGAN KEJADIAN INSOMNIA PADA MAHASISWA TINGKAT AKHIR: (Studi Kasus pada Mahasiswa Universitas PGRI Semarang) - Ifa Nurhana, Ira Puspita Sari, Rauly Sijabat (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This study aims to explore the relationship between stress levels and the incidence of insomnia in final year students at PGRI University Semarang. The impact of stress, such as mental and emotional syndromes, has become a major concern in adolescent mental health. Insomnia, as a common sleep disorder, can also affect college students' well-being. This research method is quantitative using a cross-sectional analytical research type design. The population of this study were final year students at PGRI University Semarang using Simple Random Sampling (Proportione Stratified sampling) and Purposive Sampling techniques. The results of the study showed that there was a significant relationship between stress levels and the incidence of insomnia in final year students. These findings provide valuable insight into the importance of stress management and good sleep in supporting student mental health in academic settings. The implications of this research can be used as a basis for developing intervention programs aimed at improving student welfare in higher education. It is hoped that this research can make a positive contribution to efforts to prevent and treat mental health problems among students.